On the Characteristics of Difference of Some Linear Positive Operators - Garg, Sangeeta (Asian Journal of Mathematical Sciences(AJMS), 2022)
Recently, many researchers have concerned the problems based on difference of two linear positive operators having same basis functions. In this paper, we deal with the difference of two summation integral type linear positive operators, one having different basis functions and other Durrmeyer type operators. We also obtained the difference of Baskakov operators and beta operators.